SAT0176 Smoking increases systemic lupus erythematosus susceptibility in women carrying the HLA-DRB1 risk alleles. (23rd January 2014) - Bang, S.-Y.; Lee, J.-S.; Joo, Y.-B.; Kim, J.-J.; Son, C.-N.; Jung, K.-H.; Lee, H.-S.; Bae, S.-C.
Abstract : Background: While smoking exposure has been causally linked to rheumatoid arthritis, the relationship between smoking and the development of systemic lupus erythematosus (SLE) is less clear. The major studies in patients with SLE included did not have statistically significant associations and one outlying study increased the risk for SLE in a predominately Hispanic population. Objectives: We investigated whether HLA-DRB1 risk alleles, smoking, or the combination contribute to the development of SLE and whether smoking influences the production of autoantibodies in a Korean population. Methods: A total of 877 women from BAE SLE cohort, who fulfilled the American College of Rheumatology 1997 revised criteria for SLE, and 976 healthy women were recruited in a Korean population. Four-digit HLA-DRB1 typing was performed by a conventional PCR-SBT method. Information about smoking history was obtained through a questionnaire by face-to-face interviews. Odds ratios (OR) with a 95% confidence interval (CI) were calculated. Results: The DRB1*1501 and *0803 alleles were associated with SLE susceptibility, using the relative predispositional effects according to controlling the Bonferroni method [OR 1.82 (95% CI: 1.44-2.03), p=4.45× 10 -7 and OR 1.81 (95% CI: 1.40-2.34), p=4.77×10 -6 ). The smoking had significant effects on the development of SLE [OR 2.50 (95% CI: 1.48-4.21), p=6.23×10 -4 ] adjusted for age and HLA-DRB1 risk alleles. The combination of smoking and HLA risk allele increased the risk for SLE 5.7-fold, compared with nonsmokers without carrying HLA-DRB1 risk alleles. However, interactions between HLA-DRB1 risk alleles and smoking were not observed.We found no significant relationship between smoking and the production autoantibodies, such as anti-Sm, ds-DNA, anti-Ro, anti-La, anti-RNP, or anti-phospholipid antibody in patients with SLE. Conclusions: We demonstrated that smoking increases systemic lupus erythematosus susceptibility in individuals carrying the HLA-DRB1 risk alleles. Disclosure of Interest: None Declared